Muc1 promotes migration and lung metastasis of melanoma cells - Wang, Xiaoli (Am J Cancer Res, 2015)
Early stages of melanoma can be successfully treated by surgical resection of the tumor, but there is still no effective treatment once it is progressed to metastatic phases. Although growing family of both melanoma metastasis promoting and metastasis suppressor genes have been reported be related to metastasis, the molecular mechanisms governing melanoma metastatic cascade are still not completely understood. Therefore, defining the molecules that govern melanoma metastasis may aid the development of more effective therapeutic strategies for combating melanoma. In the present study, we found that muc1 is involved in the metastasis of melanoma cells and demonstrated that muc1 disruption impairs melanoma cells migration and metastasis. The requirement of muc1 in the migration of melanoma cells was further confirmed by gene silencing in vitro. In corresponding to this result, over-expression of muc1 significantly promoted the migratory of melanoma cells. Moreover, down-regulation of muc1 expression strikingly inhibits melanoma cellular metastasis in vivo. Finally, we found that muc1 promotes melanoma migration through the protein kinase B (Akt) signaling pathway. To conclude, our findings suggest a novel mechanism underlying the metastasis of melanoma cells which might serve as a new intervention target for the treatment of melanoma.